MOTIVASI ANAK MEMILIH SEKOLAH DI PESANTREN MODERN AL-AMIN DESA RAWANG KAO KECAMATAN LUBUK DALAM KABUPATEN SIAK - Rahmat Ramadhan; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in the village of Lubuk Rawang Kao Subdistrict Siak In the object of research is children / students of class one (1), two (2), and three (3) who attend boarding schools. This study aims to look and find out what motivates the students to choose a modern boarding school in Al-Amin. The population of this study is children who were sitting in the class one (1), two (2), and three (3) Tsanawiyah Madrasa, while samples of this research are children from grade one to grade three by using the method of proportionate stratified random sampling by taking a precision of 15% of the total number of three (3) classes. Then the number of samples of this study were 37 children / students of Modern Boarding school Al-Amin. Then the data were analyzed using descriptive quantitative method. Based on the analysis, it was found that the child's motivation choose a school in modern Boarding school Al-Amin consisting of internal and external factors is dominant on the internal factors that constituted the decision themselves, interest talents, and their ideals than the external which is based on the encouragement of people parents and the influence of other friends.Keywords: Motivation schools, voters